2020
DOI: 10.1186/s12887-020-02097-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of new generation tympanic thermometry in children under different cutoffs: a systematic review and meta-analysis

Abstract: Background: The infrared tympanic thermometer (IRTT) is a popular method for temperature screening in children, but it has been debated for the low accuracy and reproducibility compared with other measurements. This study was aimed to identify and quantify studies reporting the diagnostic accuracy of the new generation IRTT in children and to compare the sensitivity and specificity of IRTT under different cutoffs and give the optimal cutoff. Methods: Articles were derived from a systematic search in PubMed, We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This procedural guideline for nurses is intended for highly dependent or critically ill infant or children who require body temperature monitoring, and according to our interpretation is applicable to the current COVID‐19 pandemic situation. This notion was also supported by a recent systematic review and meta‐analysis conducted by Shi et al (2020) that concluded that tympanic thermometry has a high diagnostic accuracy and is a good alternative for screening of the temperature in paediatric patients. The blood supply of the tympanic membrane from the common carotid artery is shared with the hypothalamus.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This procedural guideline for nurses is intended for highly dependent or critically ill infant or children who require body temperature monitoring, and according to our interpretation is applicable to the current COVID‐19 pandemic situation. This notion was also supported by a recent systematic review and meta‐analysis conducted by Shi et al (2020) that concluded that tympanic thermometry has a high diagnostic accuracy and is a good alternative for screening of the temperature in paediatric patients. The blood supply of the tympanic membrane from the common carotid artery is shared with the hypothalamus.…”
Section: Discussionmentioning
confidence: 68%
“…A large‐scale systematic review and meta‐analysis of tympanic temperature measurements involving 12 diagnostic studies that pooled 4639 paediatric patients had found that a new generation of tympanic thermometry has high diagnostic accuracy and can be a good alternative for fever screening in children (Shi et al, 2020). According to the practical guidelines recommended by the Global Heat Health Information Network, measurement of tympanic temperature, although arguably not accurate especially during the hot heat season, still has some value (Daanen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not convenient for repeated use, the rectal thermometer is generally considered an accurate reflection of the body’s core temperature[ 5 - 11 ]. Choosing the instrument for accurate measurement can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…An infrared tympanic thermometer (IRTT) is often used in children because its use is easy and rapid, and it shows a value close to the rectal temperature [ 7 ]. However, its use is restricted to children aged < 2 years because of the anatomy of the external auditory meatus [ 8 ], and its accuracy is affected by the presence of earwax in this structure [ 9 ]. In addition, using an IRTT can be stressful for children, parents, and nurses because direct contact with the thermometer disturbs sleep or provokes anxiety and fear in the child.…”
Section: Introductionmentioning
confidence: 99%